An Intensive Lifestyle Intervention Is an Effective Treatment of Morbid Obesity: The TRAMOMTANA Study—A Two-Year Randomized Controlled Clinical Trial - Bartolomé Burguera; Juan Jesús Tur; Antonio Jorge Escudero; María Alos; Alberto Pagán; Baltasar Cortés; Xavier Francesc González; Joan B. Soriano (International Journal of Endocrinology)
Bariatric surgery is currently the most effective therapy to induce weight loss in morbidly obese patients. Objective. This controlled, clinical trial with a two-year intervention was aimed at comparing the efficacy of two nonsurgical approaches versus bariatric surgery, on body weight changes and metabolic parameters in morbidly obese patients. Methods. Patients were randomized to an Intensive Lifestyle Intervention (ILI) (n=60) or Conventional Obesity Therapy (COT) (n=46). The ILI group received behavioral therapy and nutritional counseling. The COT group received standard medical treatment. They were compared with a third group, Surgical Obesity Group (SOG) (n=37). Results. Patients who received ILI had a greater percentage of weight loss than patients receiving COT (−11.3% versus −1.6%; p<0.0044). Interestingly 31.4% of patients included in the ILI group were no longer morbidly obese after just six months of intervention, increasing to 44.4% after 24 months of intervention. The percentage weight loss in SOG was −29.6% after that same period of time. Conclusions. ILI was associated with significant weight loss when compared to COT, in a group of patients with obesity. An ILI approach could be an alternative therapy to patients with obesity, who are not candidates to undergo bariatric surgery. This trial is registered with EudraCT 2009-013737-24.